Expression of growth factors and structural proteins in chordomas: Basic fibroblast growth factor, transforming growth factor alpha, and fibronectin are correlated with recurrence - (:unkn) unknown (OXFORD UNIV PRESS INC, 2002)
OBJECTIVE; To test the hypothesis that the expression of certain growth factors and/or structural proteins is correlated with the biological behavior of cranial base chordomas. METHODS: The study investigated 14 pathological specimens of cranial base chordomas from patients who were monitored for at least 2 years after their initial operations. Some cases involved multiple tumor recurrences and multiple operations. For those patients, the time to recurrence after each operation was recorded and a mean value was calculated. Nine patients with mean times to recurrence of 24 months or more or with 24 months of follow-up monitoring without recurrence after single operations were designated the good-prognosis group. Five patients with mean times to recurrence of less than 24 months were designated the poor-prognosis group. In each case, only the specimen from the initial operation was studied. Multiple sequential sections were cut from paraffin-embedded blocks of tissue and immunohistochemically prepared for detection of three growth factors and three structural proteins, i.e., basic fibroblast growth factor, transforming growth factor alpha, vascular endothelial growth factor, fibronectin, collagen III, and collagen IV. Intensity of expression was graded by using a four-tier system (Grades 0, 1, 2, and 3). Levels of expression of the molecules in the two groups were evaluated and compared. RESULTS: The mean transforming growth factor alpha expression intensity grades for the good- and poor-prognosis groups were 0.8 and 2.6, respectively, and the corresponding mean basic fibroblast growth factor grades were 1.4 and 2.6. For both groups, the mean grade for vascular endothelial growth factor expression was 0.6. For fibronectin, the mean staining grades for the good- and poor-prognosis groups were 2.2 and 3.0, respectively. The corresponding mean intensities for collagen III were 1.1 and 0.8, and those for collagen IV were 2.5 and 2.6. CONCLUSION: Our descriptive data from immunohistochemical analyses of chordomas suggest that high levels of transforming growth factor alpha and basic fibroblast growth factor expression are linked to higher rates of recurrence. Strong fibronectin expression may also be a marker of aggressive biological behavior.
Keywords: chordoma; fibroblast growth factor; fibronectin; growth factors; matrix proteins; transforming growth factor; PROLIFERATION